2009
DOI: 10.1074/jbc.m109.027706
|View full text |Cite
|
Sign up to set email alerts
|

Three-way Interaction between 14-3-3 Proteins, the N-terminal Region of Tyrosine Hydroxylase, and Negatively Charged Membranes

Abstract: Tyrosine hydroxylase (TH), the rate-limiting enzyme in the synthesis of catecholamines, is activated by phosphorylationdependent binding to 14-3-3 proteins. The N-terminal domain of TH is also involved in interaction with lipid membranes. We investigated the binding of the N-terminal domain to its different partners, both in the unphosphorylated (TH-(1-43)) and Ser 19 -phosphorylated (THp-(1-43)) states by surface plasmon resonance. THp-(1-43) showed high affinity for 14-3-3 proteins (K d ϳ 0.5 M for 14-3-3␥ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
70
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 75 publications
11
70
1
Order By: Relevance
“…Bacteria were lysed by French press, and GST–14-3-3 fusion proteins were purified on glutathione Sepharose 4B (GE Healthcare) as described previously (30). …”
Section: Methodsmentioning
confidence: 99%
“…Bacteria were lysed by French press, and GST–14-3-3 fusion proteins were purified on glutathione Sepharose 4B (GE Healthcare) as described previously (30). …”
Section: Methodsmentioning
confidence: 99%
“…TH is a cytoplasmic protein but it was also found to be membrane-bound at the brain nerve endings and synaptic vesicles1819. There is scant knowledge on the structural determinants and conformational changes occurring upon TH membrane binding, though it has been shown that the direct interaction with negatively charged membranes depends on N-terminal extension to the ACT domain2021.…”
mentioning
confidence: 99%
“…Based on the propensity of TH to bind to negatively charged membranes2021 in this work we have studied the effects that this interaction may have on membrane integrity, enzyme conformation and cellular viability. We have examined the interaction of isoform 1 of human TH (hTH1) with negatively charged liposomes using large unilamellar vesicles (LUVs).…”
mentioning
confidence: 99%
“…This mix is considered a good mimic of negatively charged physiologically relevant membranes. 30,33 Deposition of mixed polypeptide-lipid monolayer films on hydrophilic mica results in an orientation of the lipid head groups toward the mica surface. 34 Thus, the interacting polypeptides are expected to be trapped between the mica and the lipid monolayers or, alternatively, intercalated in the lipid film.…”
Section: Membrane Distortions and Formation Of Aos By Hamlet Studied mentioning
confidence: 99%